Long-term mortality in mothers with perinatal losses and risk modification by surviving children and attained education: a population-based cohort study. Issue 11 (24th November 2016) - Halland, Frode; Morken, Nils-Halvdan; DeRoo, Lisa A; Klungsøyr, Kari; Wilcox, Allen J; Skjærven, Rolv
Abstract : Objective: To assess the association between perinatal losses and mother's long-term mortality and modification by surviving children and attained education. Design: A population-based cohort study. Setting: Norwegian national registries. Participants: We followed 652 320 mothers with a first delivery from 1967 and completed reproduction before 2003, until 2010 or death. We excluded mothers with plural pregnancies, without information on education (0.3%) and women born outside Norway. Main outcome measures: Main outcome measures were age-specific (40–69 years) cardiovascular and non-cardiovascular mortality. We calculated mortality in mothers with perinatal losses, compared with mothers without, and in mothers with one loss by number of surviving children in strata of mothers' attained education (<11 years (low), ≥11 years (high)). Results: Mothers with perinatal losses had increased crude mortality compared with mothers without; total: HR 1.3 (95% CI 1.3 to 1.4), cardiovascular: HR 1.8 (1.5 to 2.1), non-cardiovascular: HR 1.3 (1.2 to 1.4). Childless mothers with one perinatal loss had increased mortality compared with mothers with one child and no loss; cardiovascular: low education HR 2.7 (1.7 to 4.3), high education HR 0.91 (0.13 to 6.5); non-cardiovascular: low education HR 1.6 (1.3 to 2.2), high education HR 1.8 (1.1 to 2.9). Mothers with one perinatal loss, surviving children and high education had no increased mortality, whereas corresponding mothers with low education had increased mortality; cardiovascular: two surviving children HR 1.7 (1.2 to 2.4), three or more surviving children HR 1.6 (1.1 to 2.4); non-cardiovascular: one surviving child HR 1.2 (1.0 to 1.5), two surviving children HR 1.2 (1.1 to 1.4). Conclusions: Irrespective of education, we find excess mortality in childless mothers with a perinatal loss. Increased mortality in mothers with one perinatal loss and surviving children was limited to mothers with low education.